PENERAPAN METODE EXPERIENTAL LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SMK KB PUSDIKPAL KELAS X TMK - Susi Agustina; Wikanengsih Wikanengsih; Diena San Fauziya (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Writing poetry in learning at school is sometimes less interested because it is considered less attractive to students. It is undeniable that writing poetry requires good imagination skills and students must open their minds widely in order to be able to write poetry with good results. One of the methods used by educators as an alternative in solving these problems is the experiential learning method. The purpose of this research is to apply the experiential learning method in improving the skills of class X TMK SMK KB Pusdikpal in writing poetry. This research is included in classroom action research (PTK). The data analysis technique used is descriptive qualitative and quantitative analysis techniques. The data analyzed were student achievement and responses to the application of the experiential learning method at SMK KB Pusdikpal class X TMK. The results of the research that have been done can be seen that the results of the acquisition of the poetry writing skills test at SMK KB Pusdikpal class X TMK in the first cycle obtained a total score of 71.7 with a sufficient category. While the results of the acquisition of skills tests in the second cycle obtained a total score of 78.3 in the good category. As for the increase in class X TMK SMK KB Pusdikpal in each cycle, namely in cycle 1 had an increase of 8.9 while in cycle II had an increase of 16.4. With the application of the experiential learning method can improve the skills of writing poetry in class X TMK SMK KB Pusdikpal.